Time series analysis of ex-vivo ischemia-reperfused heart using Q-space imaging - Genki Ichihara; Junichi Hata; Daisuke Nakashima; Kyohei Daigo; Kazuhisa Sugai; Yuji Iwasawa; Motoaki Sano; Masaya Nakamura; Hideyuki Okano; Kazuki Sato; Yoshinori Katsumata (Scientific Reports)
Abstract In the evaluation of myocardial infarction, cardiac MRI remains problematic in terms of sensitivity and quantitativeness. Thus, we sought to delineate pathological microstructural alterations across temporal phases subsequent to myocardial ischemia–reperfusion (IR) injury utilizing q-space imaging (QSI), an advanced diffusion imaging methodology proficient in assessing the non-Gaussian diffusion patterns of molecules. Rats were subjected to IR injury, and infarct was evaluated at 2, 7, and 30 days via histopathological staining and MRI using a 9.4‐Tesla system. QSI was performed with gadolinium-enhanced T1-weighted imaging (T1WI) for comparative assessment. Correlation coefficients among images were computed at each level of the left ventricular short-axis cross-section to juxtapose the infarct dimensions and morphology. Axial diffusivity of the kurtosis maps at 2, 7, and 30 days revealed substantial correlations with the hyperintense areas noted on T1WI (R2 = 0.885, 0.947, and 0.929, respectively). Furthermore, a strong correlation was noted with the transmural extent of infarction. Even in the absence of gadolinium contrast, the high-intensity regions delineated by QSI were concordant with the extent of pathological infarction (R2 = 0.977). These findings highlight the capability of QSI in identifying pathological changes at the infarct site, independent of gadolinium contrast media and irrespective of the temporal phase subsequent to the IR onset.